Microstructural analysis and blowing agent concentration in aged polyurethane and polyisocyanurate foams - Berardi, Umberto; Madzarevic, Jelena (Applied thermal engineering, 2020)
•Foams age causing a deterioration of thermal and mechanical properties with time.•Blowing agents used in polyisocyanurate foams tend to leave the material matrix.•SEM allowed to analyse the changes of the cell microstructure after accelerated aging.•SEM showed differences in cell aspect ratio and cell wall thickness in polyurethanes.•The blowing gas reduced from 11% to 85% in laboratory-aged polyisocyanurates. Over the last few years, new environmental protection regulations have promoted the adoption of new blowing agents for the production of foam materials. Understanding how these new blowing agents influence the characteristics of the foams is critical in thermal engineering applications. The cell structure of a foam and the concentration of the blowing agents in it are the main factors affecting the thermal conductivity of foams. Recent studies have revealed the risks of condensation of some of the new environmentally friendly blowing agents at temperatures below 10 °C. Meanwhile, many blowing agents tend more easily to escape the foam structure when subject to temperature cycles; this aging increases the thermal conductivity of too, since the blowing gas is replaced by air. In this paper, to understand the loss of thermal performance of aged foams, a microstructure and chemical characterization was performed together with thermal conductivity tests of both pristine and laboratory-aged foams. The aging behaviour was analysed by SEM imaging and by measuring the blowing agent concentration in both open cell and closed cell foams. Changes in the polymer physical attributes were identified. Results prove that aged foams show cellular elongation and increase in the cell wall thickness. The results of gas chromatography helped to quantify the changes in the concentration of pentane in aged polyisocyanurate foams. A decrease of the blowing agent between 11% and 85% for the aged polyisocyanurates was measured. Finally, this study highlights the importance to analyse the in-service characteristics of both polyurethane and polyisocyanurate foams to avoid considering their thermal conductivity as a constant property.